Discourse, Narrative, and Voice: The Power of Communicating Bioethics Through the Media - Gallois, Hortense (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
This perspective explores the role of the bioethicist in shaping public discourse through the media, while accounting for the power of narratives and voice.